European Registry on the management of Helicobacter pylori infection (Hp-EuReg): an analysis of 2360 patients receiving first-line therapy in Russia - O'Morain, Colm (My University, 2020)
European Registry on the management of Helicobacter pylori infection («Hp-EuReg») – a multicenter prospective observational study initiated by the European Helicobacter and Microbiota Study Group, conducted in 27 European countries in order to evaluate the real clinical practice of diagnosis and treatment of H. pylori and its comparison with international recommendations. Materials and methods. The analysis of 2360 patients entered in the register by the Russian centres of «Hp-EuReg» in 2013–2017, who were underwent 1st line eradication therapy. Results. The most common methods of primary diagnosis of H. pylori are histological (37.7%), rapid urease test (29.2%) and serology (29.7%). The duration of eradication therapy in 9.4% of cases was 7 days, in 65.3% – 10 days, and in 25.3% – 14 days. To control the effec- tiveness of treatment, H. pylori antigen in feces (31.3%), urea breath test (23.4%) and histological method (23.3%) were used. In 3.6% cases was used serology by mistake. In 17.3% of patients control was not carried out. The effectiveness of triple therapy with a PPI, amoxicillin, clar- ithromycin (per protocol) was 67.6%, with 7-day course, 81.1% at 10-day and 86.7% at 14-day course. Åradication rate of triple therapy with addition of bismuth (per protocol) reached 90,6% in the group receiving 10-day scheme and 93.6% in the group receiving the 14-day treat- ment. Conclusion. Significant deviations of clinical practice from expert recommendations, most pronounced at the stage of monitoring the effec- tiveness of therapy, were noted. The suboptimal efficacy of triple therapy is shown.
PUBLISHED [GOLD] ; Text in Russian
Keywords: Helicobacter pylori; Hp-EuReg; register; eradication therapy; Immunology, Inflammation & Infection